Information content of solicited and unsolicited rating change announcements. - Cheong, Melissa Seok Fun. (2008)
This research examines information content of rating changes in the Japanese capital market by analysing stock prices before, during and after announcements of solicited and unsolicited rating change are made. Information value of a rating change announcement is determined by examining the market’s reactions to the announcement;i.e.the stock prices.